Administrative Control and Its Role in Enhancing Employees’ Performance in Commercial Banks (A Field Study of the Opinions of a Sample of Employees in the Branches of Jumhuriya Bank in the City of Benghazi) (Al-Farooq Journal of Sciences, 2026)
This study aimed to examine the impact of the administrative control system—represented by its dimensions(control effectiveness, control objectives, and control methods)—on employees’ performance—represented by (performance evaluation, performance quality, and employee motivation)—at the branches of Jumhouria Bank in Benghazi.The study adopted a descriptive analytical approach. Data were collected from a sample of 94 employees using a structured questionnaire and analyzed using SPSS (Version 23).The results revealed a statistically significant positive relationship between the administrative control system and employees’ performance. Control effectiveness was found to be the most influential dimension, followed by control objectives, while control methods had the least relative impact. However, employee motivation showed relatively weak results compared to other performance dimensions.The study recommends strengthening motivational systems, enhancing the preventive role of administrative control, modernizing control tools through digital technologies, and promoting participatory control practices to improve overall performance and achieve strategic organizational objectives.
Keywords: Administrative control, employees’ performance, Jumhuriya Bank branches, Benghazi.